Challenges in Adaptation of Carbon Offsetting Apps by Companies for Business-Related Air Travel - Pal Singh, Agya (Digital Repository of Theses, 2025)
The global imperative to address climate change has prompted businesses to explore sustainable practices, including carbon offsetting, to mitigate the environmental impact of their operations. This research delves into the challenges encountered by businesses in adopting carbon offsetting platforms specifically for air travel-related emissions. This research is specific to challenges in adopting carbon offsetting platform for Business related air travel at it is major contributor of Greenhouse Gases (GHG) Focusing on emissions from air travel is crucial, as air travel continues to grow. According to the David Suzuki Foundation, a quarter of all emissions could be from flying by 2050" (David Suzuki Foundation, 2022). This research aims to understand the challenges and factors that impacts adoptions of carbon trading applications for business-related air travel and to build the conceptual model based on the existing studies and reports and relevant data collected by conducting Survey and interviews. In this study, we conducted an in-depth analysis of the barriers that hinder the widespread implementation of carbon offsetting initiatives within the context of business-related air travel. Through a comprehensive literature review and empirical investigation, we identified and categorized the primary challenges faced by individuals and organizations aiming to integrate carbon offsetting into their air travel practices. Result of this research will be of assistance to achieve the Sustainability goals of business organization by understanding the challenges in one of the key areas related to reducing carbon footprint. Furthermore, it will also help the Carbon offset platform companies in determining the potential solutions to the highlighted challenges. The findings reveal a multifaceted landscape of obstacles, encompassing both practical and conceptual dimensions. From a practical standpoint, complexities arise in accurately quantifying emissions, selecting appropriate offset projects, and effectively communicating the carbon offsetting process to employees and stakeholders. Moreover, challenges linked to the credibility and transparency of offset projects emerge as significant concerns. Conceptually, the research uncovers a range of psychological and organizational factors influencing the adoption of carbon offsetting platforms. These encompass issues of employee engagement, organizational commitment, and the alignment of carbon offsetting with corporate sustainability goals. Furthermore, the study highlights the tension between economic considerations and ethical imperatives, posing a dilemma for businesses seeking to strike a balance between financial viability and environmental responsibility. In conclusion, this research contributes to a deeper understanding of the barriers faced by businesses in embracing carbon offsetting for air travel-related emissions. By shedding light on the intricate interplay of practical and conceptual challenges, this study provides valuable insights for organizations, policymakers, and industry stakeholders seeking to navigate the complexities of sustainable business practices in the aviation sector. Keywords: Carbon offsetting, business travel, sustainability, environmental impact, challenges, adoption, aviation, emissions mitigation.